Uji Efektivitas Sediaan Hand Sanitizer Kombinasi Ekstrak Daun Kemangi (Ocimum Sanctum L) Dan Ekstrak Kulit Jeruk Purut (Citrus Hystrix) - Indri Kusuma Dewi; Bambang Yunianto (Poltekkes Kemenkes Surakarta, 2016)
Absctract : Antiseptic Activity, Kemangi Leaf- Cytrus Hystrix Leather, Gel Antiseptic (Hand Sanitizer). It is known kemangi leaf had contained saponins, flavonoids and tannins that benefit as antibacterial, while in research by Susanti, 2010 had proven that leather of Citrus hystrix contained essential oil as antibacterial and used as antiseptic in pharmaceutical case. So, to get the optimal formula as hand sanitizer or antiseptic gels used combination two extracts kemangi leaf and Citrus hystrix leather. This research is an experimental research with Post Test Control Group Design to analyze antiseptic activity using the Replica methods with to account the number of colonies of microorganism. Statistic test to the number of colonies of microorganism with Anova Test one way that confidence level 95% and obtained significance 0,000 the result P < 0,05 and continued to Tukey HSD test that confidence level 95%. The result statistic tes showed that have significan differences between negative control with the formula of gel antiseptic combination extract of kemangi leaf and extract Cytrus hystrix leather, so this formula have activity as antiseptic. The most effective variation concentration is concentration extract of kemangi leaf 75% and extract Cytrus hystrix leather 25%.